O orientador de aprendizagem e formação integral - Chyla, Tatiana Simas Mielke (Universidade do Vale do Rio dos Sinos, 2020)
This study is a reflection about a “new” functionality at Colégio Medianeira, the named “Orientador de Aprendizagem”, who monitors and mediates the involved personnel´s learning in the school context. Such research presents the analysis of the relationships established, through the eyes of teachers and students, from the teaching-learning process that sometimes reveal approximations and sometimes distances. This function contributes to comprehensive training, proposed by Colégio Medianeira, guided by the principles of Companhia de Jesus and assumptions of the Rede Jesuíta de Educação (RJE). Besides that, reveals the intention of having possibilities for actions that seek to break with the existing fragmentations in the teaching-learning process, which were observed from many collection instruments used in this study. That is, a discussion group of twelve students from the 8th grade classes; a discussion group of 6 teachers of that same grade; and a questionnaire applied to 184 students, of the analyzed year. The methodological approach used was the qualitative. We conclude, based on this, three elements, which stand out as essential for the actions of the Orientador de Aprendizagem: the care for the development of autonomy, the listening, and the dialogue. About the first one, caught our attention the different readings and expectations projected on the students, that however still don't seem to be sufficiently understood by the teachers and, as consequence, experienced by the students. The second action named recognized the listening as fundamental in integral training, because we identified that along the academic trajectory, some subjects got unnoticed; they are or want to be invisible, hiding their weaknesses and not feeling valued. Finally, the last action is dialogue, as a necessary path for integral learning and autonomous development. And so, we conceived an intervention proposal to articulate the collected data, which are driven by the Orientador de Aprendizagem. Such elements prove to be essential to the integral formation of teaching and learning subjects.
Keywords: Orientador de aprendizagem; Ensino-aprendizagem; Formação integral; Professor; Estudante; Teaching-learning; Integral formation; Teacher; Student; ACCNPQ::Ciências Humanas::Educação